PERLINDUNGAN HUKUM KONSUMEN LISTRIK PRABAYAR DI MAGELANG - Maulaya Adhiansyah, Siti Vickie Dina; Heniyatun, Heniyatun; Sulistyaningsih, Puji (Varia Justicia, 2017)
Along with the development of technology, PT. PLN (Persero) has developed a product called "Prepaid Electricity".Prepaid electricity PT.PLN a new service for customers to manage power consumption,that came into effect in 2008. In the course of pre-paid electricity it turns out there is still a shortage of electricity that causes consumer complaints in Magelang. Based on the existing background, the authors are interested in researching it.The problem of this thesis research is:1) How is the agreement between the electrical installation of prepaid electricity in Magelang, (2) How does the legal protection prepaid electricity consumers in Magelang, (3) What efforts were made by consumers of electricity when harmed in the use of prepaid electricity in Magelang.The method used in the preparation of this paper uses normative juridical approach. The research material used by the authors consisted of primary legal materials, secondary and tertiary.The data used is secondary data, research specifications is a research-analytical description. This study using purposive sampling method with the research tools shaped open questionnaire respondents as many as 25 people in the area of prepaid electricity consumers Magelang, interviews with officials of PLN Area Magelang and related parties.Based on the research results showed that the electricity trading mechanism consists of a new installation of electric power, electric power changes and migration electricity. Legal protection prepaid electricity include: (1) The Power Purchase Agreement (SPJBTL), these agreements can be categorized as a standard contract.If the terms of consumer protection laws, clauses in SPJBTL still containing the exoneration clause, thus infringing the rights of consumers,2)Prepaid electricity rates are more expensive than postpaid electricity, this is caused by the electrical installation is not appropriate. Another factor that is coming into effect of the tariff adjustment is affected by the dollar exchange rate, crude oil prices and inflation, causing prices to fluctuate basic tariffs, (3) Their administrative costs and of street lighting tax (PPJ) charged to electricity consumers. Token purchase electricity online through bank services is what causes the emergence of administrative costs, because the bank as a company whose orientation also for profit. If the terms of consumer protection law, the imposition of administrative costs should be the responsibility of the PLN. While RPM is set by the government tax Magelang, PLN only as the tax collector, 4)Electricity consumers are not given the right to choose when it will perform a new installation or additional power, if the terms of consumer protection laws, the violation of consumer rights. Settlement of disputes in the area of prepaid electricity Magelang, completed with a direct way between PLN and consumers. Consumers are harmed can submit a complaint directly to PLN through the contact center "PLN 123?.In principle PLN Magelang emphasizes dispute resolution deliberation, to reaching an agreement and promote justice between PLN and consumers